Symmetric and non-symmetric bis-metallylene iron complexes, precursors of iron germanide nanoparticles. Issue 64 (23rd July 2019) - Sodreau, Alexandre; Lentz, Nicolas; Frutos, Maria; Mallet-Ladeira, Sonia; Nayral, Céline; Delpech, Fabien; Madec, David
Abstract : Symmetric and non-symmetric bis-metallylene iron complexes are described. A bis-germylene Fe(CO)3 complex has been applied in the synthesis of iron germanide nanocrystals. Abstract : We report herein the synthesis of symmetric and non-symmetric bis-amidinato-germylene Fe(CO)3 complexes, as well as the preparation of the corresponding disymmetric germylene–stannylene and germylene–silylene complexes by selective displacement of a carbonyl ligand under UV-a light irradiation. The symmetric bis-germylene Fe(CO)3 complex has been applied in the synthesis of iron germanide nanocrystals.